Comparison of flow and static image cytometry in the determination of ploidy. Issue 2 (February 1993) - Lanigan, D; McLean, P A; Curran, B; Leader, M
Abstract : AIMS: To compare the efficiency of flow cytometry and computed image cytometry; and to see if a reliable set of guidelines regarding interpretation of histograms could be drawn up. METHODS: The two methods were applied to a series of 111 formalin fixed renal cell carcinomas. Data generated by both methods were compared. RESULTS: The methods agreed in 85 cases. Hypodiploidy was detected by computed image cytometry in seven cases in which flow cytometry had shown only an aneuploid peak. Aneuploidy in seven in which the corresponding flow cytometry histogram was diploid. There was an overlap in the second peak proportions on flow cytometry histograms between those classed as diploid or tetraploid by computed image cytometry. In six cases the flow cytometry histograms had unacceptably high coefficients of variation and in all of these cases computed image cytometry demonstrated aneuploidy. CONCLUSIONS: Computed image cytometry is particularly useful for clarifying difficult areas in flow histograms–specifically, high coefficients of variation, high G2M phase, as well as possible near diploid aneuploidy and hypodiploidy.